2018
DOI: 10.1111/ene.13773
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of bilateral subthalamic stimulation on alexithymia in Parkinson's disease

Abstract: This is the first report of beneficial effects of STN-DBS on alexithymia. Alexithymia was significantly associated with QoL outcome independent of anxiety, depression, mania and apathy. Our study highlights the importance of alexithymia for holistic assessments of DBS outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 57 publications
4
17
1
2
Order By: Relevance
“…In accordance with previous studies, we observed an improvement of global NMS burden in patients who underwent STN‐DBS, IJLI, and APO . Considering the relative changes and effect sizes, IJLI and STN‐DBS seemed to be favorable over APO regarding the improvement of NMSS total score.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies, we observed an improvement of global NMS burden in patients who underwent STN‐DBS, IJLI, and APO . Considering the relative changes and effect sizes, IJLI and STN‐DBS seemed to be favorable over APO regarding the improvement of NMSS total score.…”
Section: Discussionsupporting
confidence: 91%
“…In the last decade, the influence of non-motor symptoms was extensively studied [ 41 ]. However, even during the last few years, several neglected non-motor symptoms have emerged or found new spotlights [ 26 , 40 , 42 ]. Our results support the role of alexithymia as a non-motor symptom contributing to impaired quality of life in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, no intervention in PwP has been described to decrease alexithymia. Dafsari et al reported minor effects of subthalamic nucleus deep brain stimulation reducing alexithymia of PwP [ 26 ]. However, in healthy subjects, alexithymia has been modifiable by mindfulness interventions [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale subscales for anxiety and depression (HADS-A and -D) was used to examine specific mood disorders [11,42]. The HADS-A and -D subscale range from 0 (no anxiety/depression) to 21 (maximum anxiety/ depression).…”
Section: (3) Mood Disorder: the Hospital Anxiety And Depressionmentioning
confidence: 99%